2011
DOI: 10.1097/aap.0b013e318235f566
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison Between Subepineural and Conventional Ultrasound-Guided Popliteal Sciatic Nerve Block

Abstract: Compared with separate injections around the tibial and peroneal divisions, a single subepineural injection at the neural bifurcation provides a higher success rate and requires shorter performance, onset, and total anesthesia-related times. Further studies are required to validate the safety of the subepineural technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 22 publications
3
69
2
Order By: Relevance
“…No motor response to nerve stimulation was observed. The onset time for surgical block in the subparaneural group was shorter than in the extraneural group (respectively, median [range] values at 11 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] minutes and 17 minutes, for surgical block excluding the 6 failure patients), and sensory blockade of the tibial nerve lasted longer. With regard to the failure rate, the 6 patients presenting block failure (incomplete sensory blockade after 30 minutes) belonged to the extraneural group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No motor response to nerve stimulation was observed. The onset time for surgical block in the subparaneural group was shorter than in the extraneural group (respectively, median [range] values at 11 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] minutes and 17 minutes, for surgical block excluding the 6 failure patients), and sensory blockade of the tibial nerve lasted longer. With regard to the failure rate, the 6 patients presenting block failure (incomplete sensory blockade after 30 minutes) belonged to the extraneural group.…”
Section: Resultsmentioning
confidence: 99%
“…During the procedure, all patients received sedation via target-controlled infusion (propofol, Marsh model, concentration at the site of action 1.2 ng/mL). Ultrasound-guided lateral, short-axis, in-plane sciatic popliteal nerve blocks (linear array probe LA 435K, [8][9][10][11][12][13][14][15][16][17][18] MHz; Agile, Kontron Medical, France) were performed by anesthetists with more than 3 years' experience with ultrasoundguided blocks. The skin was prepared with an alcoholic povidoneiodine solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the increased resolution of US machines, LA injection inside this paraneural sheath is now possible. In 2011, Tran et al 196 compared a single LA injection inside the common paraneural sheath at the sciatic nerve bifurcation (ie, the subparaneural technique) with targeted supraparaneural injections around the TN and CPN. These authors observed that the subparaneural technique resulted in a higher success rate (84% vs 56%; p=0.032) as well as improved efficiency (decreased performance/onset/total anesthesia-related times and fewer needle passes).…”
Section: Nerve Blocks Of the Sacral Plexusmentioning
confidence: 99%
“…Some have suggested that ultrasound imaging does not have the ability to differentiate the epineurium from the complex fascial layer encompassing the sciatic nerve [4] . Others suggest that these two layers are the same [12] . In conclusion, this debate suggests that ultrasound technology has limitations in detecting exactly where local anesthetic is being injected in relation to tissue planes that currently require histological analysis to clearly define [10] .…”
Section: Discussionmentioning
confidence: 99%